1990
DOI: 10.1002/jlcr.2580280605
|View full text |Cite
|
Sign up to set email alerts
|

Synthese du methyl [(chloro‐2 ethyl)‐3 nitroso‐3 ureido]‐3 didesoxy‐2, 3 α‐Darabino‐hexopyrannoside marque AU carbone‐14 OU AU carbone‐13 (CY 233 ‐ SR 90098)

Abstract: CY 233 (Ecomustine or SR 90098) is a new antitumour nitrosourea :it is characterized by a 2-chloroethylnitrosourea substituent on a dideoxycarbohydrate. It has been labelled with 14C on a) the carbonyl group of the urea in four stages starting with '*COC12, b) the second carbon of the chloroethyl group in four stages starting with [14C] ethanolamine, and c) on the methyl group on the anomeric centre of the carbohydrate in three stages starting with 14CH30H. The final position was also labelled with I3C startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…408 The syntheses of 14 C-or 13 C-labeled 498 which can be used for biochemical mechanism studies was reported. 412 In this work, the radioactive label was placed either on the carbonyl group of the urea, the second carbon of the chloroethyl group, or the glycosidic methyl group.…”
Section: Structural Variations Of the C3-nitrosoureasmentioning
confidence: 99%
“…408 The syntheses of 14 C-or 13 C-labeled 498 which can be used for biochemical mechanism studies was reported. 412 In this work, the radioactive label was placed either on the carbonyl group of the urea, the second carbon of the chloroethyl group, or the glycosidic methyl group.…”
Section: Structural Variations Of the C3-nitrosoureasmentioning
confidence: 99%